2020
DOI: 10.2478/inmed-2020-0109
|View full text |Cite
|
Sign up to set email alerts
|

Two Pandemics Coalition: Covid-19 and Obesity

Abstract: COVID-19 epidemic caused by an influenza-like virus strain (SARS-CoV-2) invaded the world. The World Health Organization (WHO) announced this infection outbreak as a global pandemic on 11 March 2020. From one day to another the number of new cases is growing and also the number of deaths. This infection emerged earlier in Wuhan City and rapidly spread throughout China and around the world since December 2019. Another silent pandemic disease spreading mainly in industrialized countries is obesity. The best exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Meanwhile, each study’s characteristics related to study design characteristics of the patients and location of the study. We specified the extracted comorbidities of cardiovascular disease, hypertension, and dyslipidemia by other systematic reviews and meta-analysis according to the recognized co-morbidities for obesity and COVID-19 [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, each study’s characteristics related to study design characteristics of the patients and location of the study. We specified the extracted comorbidities of cardiovascular disease, hypertension, and dyslipidemia by other systematic reviews and meta-analysis according to the recognized co-morbidities for obesity and COVID-19 [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The coronavirus disease (COVID-19) pandemic is triggered by the influenza-like strain of the virus (SARS-CoV-2) [ 15 ] that causes acute respiratory infection, including a wide range of diseases, from asymptomatic infection to severe acute respiratory damage, in about 20% of patients receiving healthcare [ 16 , 31 ]. The WHO has been notified on 31 December, 2019 that a new virus belongs to the coronavirus family [ 32 ].…”
Section: Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that people tend to consume delicious foods with high energy content, especially during periods of high anxiety and stress levels such as the Covid 19 pandemic [28]. The pandemic period has started to be counted as an obesogenic environment due to the negative effects on the physical activity levels as well as the negative effects on the eating habits [29]. Studies have shown that stress stimulates the consumption of delicious food in approximately 30% of the population [30,31].…”
Section: Discussionmentioning
confidence: 99%